The Anxiety Caused by the COVID-19 Pandemic on a Sample of High School Students in Public Education in Jeddah after Returning Back to School: Case Study - Alsubaie, Norah Dakhilallah; Almudhi, Hafsa Saleh; Kutbi, Alaa Ibrahim (Journal of Educational and Psychological Sciences, 2023)
The study sought to reveal the impact of psychological anxiety of the COVID-19 pandemic on secondary school students after returning to school. It also sought to identify psychological anxieties among female students by understanding the impact of the pandemic on the social, academic, and physical aspect of students and the behaviors that occurred after the pandemic. This was done by following the qualitative approach case study. To reach the results of the study, the researchers chose four cases from the 28th high school and applied the methods used in the corresponding observations and references to the academic record as research tools. The results of this study found that there was an impact of psychological anxiety due to the COVID-19 pandemic on student social relations, their desire to seek help, and daily social attitudes in school. The behavior of female students was affected, and their concern for precautionary measures increased. Also, the health of the physical students in terms of energy and immunity was somewhat affected, while the academic aspect of the students was not affected. This study also produced many recommendations, the most important one is educating students and parents about the effects of the Corona pandemic on the psychological, social and physical aspects and how to deal with them. In addition, it recommended providing schools with psychosocial specialists to support and advise students.
Keywords: Anxiety; Returning to School; High School Students; Corona Pandemic; COVID-19